Fenomena â€œCitayam Fashion Weekâ€ Dalam Perspektif Komunikasi Artifact - Syatria Budianto; Fifi Hasmawati; Muslimin (CV. ITTC INDONESIA, 2023)
The Citayam Fashion Week phenomenon is an activity where teenagers from Jakarta and its surrounding areas such as Citayam, Bojong Gede and Depok gather to express their unique fashion styles. As if continuing Paris Fashion Week, which turned the streets into catwalks, they took turns showing off their clothes at the Sudirman (Zebra Cross) crossing. They express themselves through the clothes they wear, this is also known in communication science as artifact communication. Artifact communication is defined as any form of appearance, such as hair, cosmetics used on clothing, bags, values, signs, and other characteristics that evoke positive or negative reactions to the recipient's appearance, whether clichÃ©d, a fixed image that does not change and does not respond to appearance. certain view. This study uses qualitative research methods by conducting literature studies, observations, and data triangulation. From this research, it can be concluded that the Citayam Fashion Week phenomenon in an artifact perspective is a forum for self-expression of adolescents about their interest in fashion with clothes that are what they are but can be created to be interesting things.